Semantic Parallelism in Traditional Kakataibo Chants - Prieto Mendoza, Alejandro Augusto (2019)
In the present article, I propose some initial topics for the typological-comparative study of semantic parallelism, which also serve as an analytical axis to study semantic parallelism in traditional kakataibo chants. These basic topics are the structure of the cotext, lexical and grammatical type of parallel units, type of semantic relations between parallel units, number of parallel units per pair of lines, and associated phenomena such as recurrent or fixed pairing and diphrasism. Following this initial proposal, I postulate that the cotext in Kakataibo semantic parallelism is a repeated morphosyntactic structure that does not exhibit ellipsis or increasing, the number of parallel units can be one to three slots and one pair is more productive, parallel units are related by semantic fields such as kinship terms and colors. Furthermore, I analyze the interaction of semantic parallelism in the continuous creation of lines with two other poetic forms, enjambment and repetition, and I postulate that semantic parallelism is a compositional strategy due to its high productivity for line composing.